META-ANALISIS: PENERAPAN E-MODUL BERBASIS EXE-LEARNING DALAM PEMBELAJARAN IPA - Indri Mardiyatus Soleha; Hadma Yuliani; Jhelang Annovasho (Jurnal Sains dan Pendidikan Fisika, 2023)
This study aims to estimate the application of  exe-learning-assisted e-modules  in science learning in Indonesia. This meta-analysis research method includes problem formulation, data collection (study), data coding, data analysis, and interpretation. After searching for journals, 16 journals were found that discussed the application of  exe-learning-assisted e-modules in science learning. Of these, 6 articles meet the established criteria, namely research using  exe-learning-assisted e-modules  in science learning in Indonesia. The results of this study revealed that there was a significant positive effect in the application of  exe-learning-based e-modules in science learning. The research findings showed that the results of the meta-analysis showed  an effect size  value of 0.9, which indicates a high level of effectiveness of 82% in improving learning abilities and outcomes.